Effect of work rotation and training on employee performance (Study at PT Pegadaian (Persero) Palembang Regional Office) (Asian Journal of Economics and Business Management, 2022)
This study discusses the effect of job rotation and training on employee performance at PT. Pegadaian (Persero) palembang regional office. PT. Pegadaian (Persero) is one of the non-banking institutions that provide credit to the public for mortgage laws in Indonesia. Job rotation is a complicated problem for employees, especially those not ready for new changes. Employees become anxious when they have to be transferred to a new position and face unfamiliar work challenges. The training program is still not effective and efficient, especially in training with virtual methods, which usually use the zoom meeting application. Performance appraisal is carried out transparently and objectively. At the beginning of each financial year, Pegadaian sets a Key Performance Indicator (KPI) for each work unit. The sample in this study was 175 respondents with a non-probability sampling with a purposive sampling method—a data collection method using primary data. Analysis of the data used is multiple linear analysis and t-test. The results of this study are that job rotation has a significant positive effect, and training has a significant positive effect on employee performance. This research suggests that job rotation must be scientific and objective and increase productivity and reduce employee burnout. The training program must be appropriate to the needs and values of the employee's job. Then, superiors should give new challenges or assignments and be accompanied by additional compensation for employees so that it can attract employees to always look for new challenges in their work and reduce employee complaints about things that are not important at work.